2010
DOI: 10.3727/096368910x514648
|View full text |Cite
|
Sign up to set email alerts
|

Global Contractility Increment in Nonischemic Dilated Cardiomyopathy after Free Wall-Only Intramyocardial Injection of Autologous Bone Marrow Mononuclear Cells: An Insight over Stem Cells Clinical Mechanism of Action

Abstract: Bone marrow mononuclear cells (BMMC) effects have been investigated in small series of nonischemic dilated cardiomyopathy (NIDC). Left ventricular myocardial contractility improvements occur, but doubt remains about their mechanism of action. We compared contractility changes in areas treated (free wall) and nontreated (septal wall) with BMMC, in selected patients who have showed significant ventricular improvement after free wall-only intramyocardial stem cells injection. From 15 patients with functional clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
(32 reference statements)
0
13
1
Order By: Relevance
“…This was also observed in the study by Beeres et al 24 The study by Sant'anna et al in DCM also suggests that the effects of stem celledirected therapy in terms of contractile improvement were not limited to the area of injection but more diffuse in nature, suggesting a more diffuse mechanism of action rather than a local effect. 25 In a preclinical model of DCM, stem cell transplantation has been shown to improve cardiac function not only through induction of angiogenesis, but also by means of their ability to supply large amounts of angiogenic, antiapoptotic, and mitogenic Values are presented as mean 6 SD or n (%).…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed in the study by Beeres et al 24 The study by Sant'anna et al in DCM also suggests that the effects of stem celledirected therapy in terms of contractile improvement were not limited to the area of injection but more diffuse in nature, suggesting a more diffuse mechanism of action rather than a local effect. 25 In a preclinical model of DCM, stem cell transplantation has been shown to improve cardiac function not only through induction of angiogenesis, but also by means of their ability to supply large amounts of angiogenic, antiapoptotic, and mitogenic Values are presented as mean 6 SD or n (%).…”
Section: Discussionmentioning
confidence: 99%
“…9 Similarly, direct transthoracic IM injection of bone marrow mononuclear cells has been associated with global contractility increment in patients with DCM. 10 At this time, it remains uncertain whether transendocardial stem cell delivery in patients with DCM is associated with greater retention and improvement in ventricular function than intracoronary delivery. To resolve this question, in this study, we sought to determine whether transendocardial stem cell delivery is associated with a greater retention rate and clinical improvement than intracoronary stem cell delivery in patients with DCM.…”
Section: Vrtovec Et Al Stem Cell Delivery In Dilated Cardiomyopathy S43mentioning
confidence: 99%
“…15,16 The research results on outcomes of stem cell injection for DCM were limited. [17][18][19][20][21][22] Roura S, et al, demonstrated defective vascularization and impaired vasculogenesis (the de novo vascular organization of mobilized endothelial progenitors) and angiogenesis in dilated cardiomyopathy patients. The defective vascularization was associated with reduced myocardial expression of vascular β-catenin, an important angiogenic regulator.…”
Section: Discussionmentioning
confidence: 99%